2021
DOI: 10.3389/fpsyg.2021.695067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence, the Teacher-Student Relationship, and Flourishing on Academic Performance in Adolescents: A Moderated Mediation Study

Abstract: Educational context has an important influence on adolescents’ development and well-being, which also affects their academic performance. Previous empirical studies highlight the importance of levels of emotional intelligence for students’ academic performance. Despite several studies having analyzed the association and underlying mechanisms linking emotional intelligence and academic performance, further research, including both personal and contextual dimensions, is necessary to better understand this relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 51 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…One of the concepts that has received increasing attention from educational contexts is the so–called flourishing (e.g., De la Fuente et al, 2017 ; Shoshani and Slone, 2017 ; Datu, 2018 ; Garzón–Umerenkova et al, 2018 ; Datu et al, 2019 ; Chamizo–Nieto et al, 2021 ; Holliman et al, 2021 ). Flourishing is synonymous with a high mental well–being level and reflects positive mental health and positive development ( Huppert and So, 2013 ; Hone et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the concepts that has received increasing attention from educational contexts is the so–called flourishing (e.g., De la Fuente et al, 2017 ; Shoshani and Slone, 2017 ; Datu, 2018 ; Garzón–Umerenkova et al, 2018 ; Datu et al, 2019 ; Chamizo–Nieto et al, 2021 ; Holliman et al, 2021 ). Flourishing is synonymous with a high mental well–being level and reflects positive mental health and positive development ( Huppert and So, 2013 ; Hone et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent positive education research has shown that flourishing is positively related to desired academic outcomes, such as performance ( Datu, 2018 ), personal resources ( Ouweneel et al, 2011 ), engagement ( Datu, 2018 ), achievement goal orientation ( Datu et al, 2019 ), adaptability and social support ( Holliman et al, 2021 ), positive teacher–student relationships ( Chamizo–Nieto et al, 2021 ), basic psychological needs ( Herrera et al, 2021 ), and passion for learning ( Chen et al, 2021 ). Conversely, it is negatively related to undesired academic outcomes, such as depression and distress ( De la Fuente et al, 2017 ), procrastination ( Garzón–Umerenkova et al, 2018 ), and psychotic experiences ( Oh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an increase in teacher support and reassurance was documented during the virus outbreak [161]. Therefore, this could further facilitate student adjustment, well-being, and academic achievement [162,163]. According to Chamizo-Nieto and colleagues [163], it would be interesting to examine whether this will last in the post-COVID-19 period.…”
Section: Benefit To Relationshipsmentioning
confidence: 99%
“…In relation to academic performance, empirical evidence shows the probability of low academic performance associated with subject failure when school bullying is persistent (Rusteholz et al 2021). An optimal relationship with teachers affects school performance (Chamizo-Nieto et al 2021). Behavior and discipline may also be associated with other variables, such as the motivational climate in the classroom (Patel 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The students assaulted had higher rates of absenteeism because of the manifest fear and perceived insecurity in the school environment with disastrous repercussions on school performance (Hammig and Jozkowski 2013). Increasing student teacher interaction can have great benefits in students with low emotional intelligence (EI), as it has positive effects on their well-being and academic performance (Chamizo-Nieto et al 2021).…”
Section: Introductionmentioning
confidence: 99%